The illustrated Al : the songs of "Weird Al" Yankovic - Yankovic, Al, 1959- (Z2 Comics, 2022)
"Winner of five Grammy Awards and 11 notations, "Weird Al" Yankovic has written some ALL of the greatest songs of both the 20th and 21st centuries."--